The Pedagogical Reformulation of International Human Rights Law Education in Asia: Where Tradition Meets Innovation - Chen, Si (Indonesian Journal of International Law, 2022)
This article explores the feasibility, challenges, and directions for pedagogical reformulation to make international human rights law compelling for Asian law students. Pedagogies are crucial for improving students’ learning effectiveness, achieving the goal of legal education, and supporting students in their career plans. The article underlines that traditional lecture-based pedagogy is insufficient to prepare law students for human rights-related international professional careers. This article argues that pedagogies in international human rights law education need to be reformulated for a better future for legal education in Asia. It builds on three sets of sources concerning teaching, researching, and practicing international law in an era of globalization: (a) an extensive literature review on legal education in the global context; (b) a close engagement with emerging literature on innovative pedagogies in legal education; and (c) the author’s personal experience at law schools and international organizations in Asia, Europe, and North America. The article showcases the ongoing pedagogical reformulation in legal education through examples in and outside Asia. It identifies two alternative pedagogies for international law education in Asia: the flipped classroom method and the problem-based learning method. Furthermore, this article develops a four-step framework for problem-based learning in a flipped international human rights law classroom. The proposed pedagogical reformulation challenges the well-established traditional pedagogical approach in the global context. However, the reformulation is not only desirable but also necessary and rewarding to foster a better future for international law education in Asia.